Analisis Faktor Persepsi Manfaat Dan Kemudahan Dalam Adopsi E-Retribusi Pasar: (Studi Literatur Berbasis Technology Acceptence Model Di Kota Bandung) - Dewi Nurmala Sari; Ajeng Kusuma Andaning; Ayu Widowati Johannes; Tati Sarihati (Program Studi Keuangan Publik, 2025)
ABSTRACT Digitizing market levies through the e-retribution system is a key strategy for the Bandung City Government to improve transparency, accountability, and Regional Original Revenue (PAD). However, the system's success depends not only on technological infrastructure but also on the acceptance of market traders as primary users. This article aims to analyze the factors of perceived usefulness (PU) and perceived ease of use (PEOU) in the adoption of e-market levies in Bandung City, as well as to identify external barriers influencing technology acceptance. The method used is a systematic literature review using the PRISMA approach, analyzing 23 selected primary and secondary documents (published between 2018 and 2024) using thematic analysis techniques based on Davis's (1989) Technology Acceptance Model (TAM) framework. The findings indicate that PU and PEOU are the primary determinants of acceptance, but their effectiveness is significantly mediated by three external factors: (1) training intensity and methods, (2) level of trust in the system and institutions, and (3) disparities in digital literacy between generations. Bandung City's Regional Original Revenue (PAD) data (2021–2024) shows an increase in the contribution of e-retribution from 44% to 90%, but resistance persists, particularly among older vendors who find the system complicated and unuser-friendly. Theoretically, this study extends the TAM model by integrating contextual variables such as digital literacy, institutional trust, and community mentoring models relevant to the context of local e-government and non-technical user groups in developing countries. Practically, these findings recommend evidence-based policies: (1) redesigning the e-retribution application using universal design principles; (2) institutionalizing the